INTEGRASI NILAI-NILAI MODERASI BERAGAMA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 6 SUKADANA KELAS VII - Ahmad Akbar; Faizal Amin; Zaenuddin, Zaenuddin (Journal of Innovation Research and Knowledge, 2024)
This study aims to analyze the application of religious moderation values in the subject of Islamic Religious Education and Character for seventh-grade students at SMP. Using a library research approach and in-depth analysis, this study concludes that there are three effective integration patterns for use in religious moderation-based PAI teaching.First, the integration of religious moderation values through Basic Competencies (KD) and Core Competencies (KI) that include moderation values. This involves the preparation of syllabi and lesson plans that incorporate religious moderation values into every aspect of teaching, from objectives to evaluations.Second, integration through experiential learning. In this approach, students are actively involved in activities that encourage the application of moderation values in everyday life, such as social projects, group discussions, and simulations of conflict situations requiring resolution based on moderation principles.Third, integration through the hidden curriculum collectively implemented by all school elements. The hidden curriculum includes school culture, teacher attitudes and behaviors, and extracurricular activities, all aimed at reinforcing religious moderation values within the school environment.With the implementation of these three integration patterns, it is hoped that students can internalize religious moderation values and apply them in their daily lives, thus creating a harmonious and tolerant environment both in school and in the community